2019
DOI: 10.1021/jacs.9b03965
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Blocked Magnetic Nanoparticles Based on Ferrite Promoted by a Three-Step Thermal Decomposition Process

Abstract: Exchange coupled nanoparticles that combine hard and soft magnetic phases are very promising to enhance the effective magnetic anisotropy while preserving sizes below 20 nm. However, the core−shell structure is usually insufficient to produce rare earth-free ferro(i)magnetic blocked nanoparticles at room temperature. We report on onion-type magnetic nanoparticles prepared by a three-step seed mediated growth based on the thermal decomposition method. The core@shell@shell structure consists of a core and an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…Furthermore, it may also partially account from the high content of Fe 2+ . 39 These results confirm those of Lopez-Ortega et al 52 who reported cell parameters of 8.40-8.42 Å for Co0.6-0.7Fe2.4-2.3O4 nanoparticles of different sizes.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, it may also partially account from the high content of Fe 2+ . 39 These results confirm those of Lopez-Ortega et al 52 who reported cell parameters of 8.40-8.42 Å for Co0.6-0.7Fe2.4-2.3O4 nanoparticles of different sizes.…”
Section: Resultssupporting
confidence: 90%
“…The interface exchange coupling in core/shell NPs provides an additional degree of freedom to control the magnetic properties of nanostructures 37,39,55 and can be exploited, for example, to enhance the anisotropy energy avoiding an undesired increase in the NP size. 56 Therefore, our next step was to identify to what extent our system would allow for control over the magnetic moment and anisotropy by performing dc magnetometry experiments, which are summarized in Figure 3 and Figure S4. The lowtemperature curves shown in Figure 3a indicate a single reversal process for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Hard–soft exchange couplings at Fe 3 O 4 ‐Co doped ferrite and Co‐doped ferrite‐Fe 3 O 4 interfaces largely influenced the superparamagnetic blocking temperature and magnetization hysteresis loops. [ 163 ] Despite being a promising approach, one has to bear in mind that synthesis of multi layered nanoparticles is much more challenging than those iron oxide nanoparticles formed via one‐pot reactions.…”
Section: Defect‐engineering In Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Recently, trimagnetic Fe3O4-CoO-Fe3O4 core-shell-shell nanoparticles have been developed via seed-mediated thermal decomposition synthesis. Hard-soft exchange couplings at Fe3O4-Co doped ferrite and Co-doped ferrite-Fe3O4 interfaces largely influenced the superparamagnetic blocking temperature and magnetization hysteresis loops [148] .…”
Section: Structural Defects Associated With Interfaces and Dopingmentioning
confidence: 99%